ENDODONTIC TREATMENT OF UPPER FIRST PREMOLAR WITH 3 ROOT CANALS - Travassos, Rosana Maria Coelho; da Paz, Eliana Santos Lyra; do Nascimento, Alexandre Batista Lopes; dos Santos, Pedro Guimarães Sampaio Trajano; de Freitas, William José Lopes; Prosini, Priscila; Alves, Josué; de Araújo, Luciane Farias; da Silva, Victoria Caroline; Martins, Wiliam Wale Rodrigues; Lima, Samuel Nogueira; de Souza, Pedro Henrique Pereira; et al. (LUMEN ET VIRTUS, 2025)
This case report highlights the successful non-surgical endodontic treatment of a maxillary first molar with unusual morphology. The treatment was performed with special C-Pilot and Glide Path files to obtain patency, and a rotary mechanized system, Sequence Rotary File from MK Life, with 2.5% Sodium Hypochlorite as an irrigating solution. The obturation was performed using the single cone technique associated with Sealer Plus sealer. It is concluded that a thorough knowledge of the variations in root canal anatomy is necessary for the success of the endodontic procedure.